The China Museum Boom: soft power and cultural nationalism. Issue 1 (2nd January 2021) - Zhang, Fenghua; Courty, Pascal
ABSTRACT: We document major changes in museum supply in China between 1996 and 2015. These years have seen the opening of many small, low budget and locally managed museums; an increase in the average size and expenditure of all museums; and significant investments in a few large and centrally managed superstar museums. Chinese people have access to larger and better museums and pay lower admission fees. Regional inequalities in museum growth are smaller than inequalities in GDP growth. We relate these findings with the small literature on Chinese museums and specifically the notions of soft power and cultural nationalism.